2005
DOI: 10.1016/j.cellbi.2005.03.020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of human dental follicle cells with dexamethasone and insulin

Abstract: The dental follicle is an ectomesenchymally derived connective tissue harboring precursor cells for the tooth supporting apparatus. In this study, we examined gene expression of freshly isolated human dental follicle cells during osteogenic differentiation in vitro. These plastic adherent fibroblastic cells express Notch-1, nestin and vimentin. We differentiated dental follicle cells with dexamethasone or insulin-based protocols into membrane-like structures containing mineralizing foci. An analysis of mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 25 publications
2
78
2
2
Order By: Relevance
“…BMPs, and more specifically BMP-2, have potent effects in inducing osteoblast differentiation of different cell sources [14,19,20,46,53]. Several studies have demonstrated dexamethasone (DEX) as a non-GF can induce terminally differentiated osteoblasts [18,36,42].…”
Section: Introductionmentioning
confidence: 99%
“…BMPs, and more specifically BMP-2, have potent effects in inducing osteoblast differentiation of different cell sources [14,19,20,46,53]. Several studies have demonstrated dexamethasone (DEX) as a non-GF can induce terminally differentiated osteoblasts [18,36,42].…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable to our previous investigations. Here, OCN was also imbedded in the extracellular matrix of DFCs after the osteogenic differentiation (Morsczeck et al 2005b). We suppose that DFCs secrete constitutively OCN into the cell culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of osteoprotegerin (OPG) reduced in the dental follicle of the first mandibular molar of the rat at day 3 postnatally, then expressed consistently up to day 10 ( Wise et al, 2000). In fact, there have been many studies which have concentrated on the important molecules promoting the differentiation of dental follicle cells in vitro (Zhao et al, 2002;Morsczeck et al, 2005;Chen et al, 2007;Kémoun et al, 2007). With the concerns above, detection methods both in vivo and vitro were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that vascular endothelial growth factor (VEGF), dexamethasone/insulin, bone morphogenetic protein 2 (BMP2) and bone morphogenetic protein 7 (BMP7) can promote cementoblast/osteoblast differentiation of DFCs (Zhao et al, 2002;Morsczeck et al, 2005;Chen et al, 2007;Kémoun et al, 2007). In tooth eruption, cytokines such as colony-stimulating factor 1 (CSF-1) and its receptor, interleukin-1 (IL-1) and its receptor, endothelial growth factor (EGF), monocyte chemoattractant protein 1 (MCP-1) and nuclear factor-κB (NF-κB) were noted for their involvement in the dental follicle, in which they combine to form a complicated tooth eruption network system (Lin et al, 1996;Wise et al, 1997;Xu et al, 1998;Que et al, 1998;Grier et al, 1998;Que et al, 1999;Gu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%